Occurrence of Ticks and Tick-Borne Pathogens During Warm Winter—A Snapshot from Central Europe - Weronika Buczek; Alicja Buczek; Marek Asman; Agnieszka Borzęcka-Sapko; Ewelina Minciel; Jadwiga Grzeszczak; Katarzyna Bartosik (Pathogens)
Background: Climate warming and anthropogenic environmental changes impact the spread of ticks and tick-borne pathogens (TBPs). This study investigated the occurrence of ticks and the risk of TBPs infection in urban and rural recreational areas in Eastern Poland at record-high temperatures in winter. Methods: Ticks were collected from vegetation using the flagging method. Various types of polymerase chain reactions were applied to detect Borrelia burgdorferi s.l., Anaplasma phagocytophilum, Rickettsia spp., and Babesia spp. in the studied ticks. Results: 268 ticks were sampled in the four urban/suburban and one rural sites, including 78 Ixodes ricinus specimens and 190 Dermacentor reticulatus ticks. Of the ticks, 49.19% were infected by at least one TBP, including 41.03% of I. ricinus and 63.04% of D. reticulatus specimens. Co-infections with TBPs that involved only I. ricinus were recorded in 6.41% of these ticks. Conclusions: The study indicates that hosts are exposed to tick attacks and TBPs infection in Central Europe at high temperatures in winter. The high activity of ticks may increase the incidence of tick-borne diseases in humans and companion animals. The record’s importance indicates that practical preventive measures against TBPs should be taken due to weather conditions rather than the season.